2022
DOI: 10.1136/bmjopen-2021-048664
|View full text |Cite
|
Sign up to set email alerts
|

Culturally adapted pulmonary rehabilitation for adults living with post-tuberculosis lung disease in Kyrgyzstan: protocol for a randomised controlled trial with blinded outcome measures

Abstract: IntroductionPulmonary rehabilitation (PR) is a programme of individually prescribed physical exercise, education and self-management activities. PR is recommended in international guidelines for managing chronic obstructive pulmonary disease (COPD) and other chronic respiratory diseases. PR is still under-recognised in tuberculosis (TB) guidelines and PR is not available in many low and middle-income countries and for people with post-TB lung disease (PTBLD). The main aims of the study are to adapt and define … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Similar studies also confirmed that respiratory function exercises, as a nonpharmacological treatment method, are simple, easy to learn, noninvasive, painless, and cost-effective. [16][17][18][19] These exercises not only alleviate clinical symptoms but also significantly enhance the psychological well-being and quality of life of patients. Therefore, medical staff should provide individualized instruction based on the specific condition of each patient, including one-on-one guidance on respiratory function exercises.…”
Section: Patients With Higher Depression Levels Exhibit Lower Respira...mentioning
confidence: 99%
“…Similar studies also confirmed that respiratory function exercises, as a nonpharmacological treatment method, are simple, easy to learn, noninvasive, painless, and cost-effective. [16][17][18][19] These exercises not only alleviate clinical symptoms but also significantly enhance the psychological well-being and quality of life of patients. Therefore, medical staff should provide individualized instruction based on the specific condition of each patient, including one-on-one guidance on respiratory function exercises.…”
Section: Patients With Higher Depression Levels Exhibit Lower Respira...mentioning
confidence: 99%